INVESTIGATING THE POLITICAL FACTORS OF AFGHAN MIGRATION - (:unkn) unknown (My University, 2020)
The purpose of this article is to determine the factors that have contributed to the migration of Afghans will be reviewed what conditions do Afghans have to migrate to other countries? In this paper, both descriptive and analytical methods used data collected from scientific books and international papers use and the immigration department Afghanistan has been collected. One of the most important factors in migration is war. More than three decades of war, insecurity, violence, and immigration have continued in Afghanistan. When immigration movement in the recent case examined Afghanistan, have with highest numbers of immigrants resulting in the melting of human resources. The spirit of tragedy young force it to leave the country. Due to security issues are characteristic of Afghan migration have been political, security, social continuation of the war has caused, the foundation ofeconomic, political, and cultural has made it difficult ethnic differences. Continue targeted killings the lack of political stability in the country distrust for bright future, intensifying the war it can be said to affect migration, the most problems of people’s threat and increasing numbers of Taliban. ISIS and al-Qaeda with internal and external networks it was supported anti-human activity on the other proxy war between the countries in the region interests. They are held in common in Afghanistan, because of the complexity of the situation it has become security and politics in the country decrease government sovereignty, security threats massacre of people, the air result attacks, suicide blast, kidnapping this has been going on for several years. That made people's optimism for a stable future unlikely. These are all factors that affect the migration of Afghanistan is the second largest immigrant country after Syria.